Simple preparation of hollow carbon sphere via templating method - Joo, Ji Bong; Kim, Pil; Kim, Wooyoung; Kim, Jongsik; Kim, Nam Dong; Yi, Jongheop (Current applied physics, 2008)
The hollow carbon sphere (HCS) was synthesized using silica particle and sucrose as a template and carbon precursor, respectively, under a hydrothermal condition. The prepared HCS were characterized by SEM, TEM and N2 adsorption. The prepared HCS showed uniforms size and high mesoporosity. It was found that the presence of acidic site on the silica particle templates would be crucial for the preparation of the HCS. Without the acidic site on silica particles, the macroporous carbon with high microporosity was prepared. It was found that the method employed in this work was highly suitable for the preparation of monodisperse HCS.